Therapeutic rigid bronchoscopy for endobronchial glomus tumors: a case series - Rong Lih Ho; Byeong-Ho Jeong; Joungho Han; Hojoong Kim (BMC Pulmonary Medicine)
Abstract Background Glomus tumors (GTs) are rare, comprising only 2% of all soft tissue tumors. Pulmonary GTs are exceptionally rare, with fewer than 80 cases reported to date. Little is known about the therapeutic outcomes of rigid bronchoscopy for endobronchial GT. Methods This is a case series of four patients with endobronchial GT who underwent therapeutic rigid bronchoscopy between February 2021 and June 2024. Results The ages of the patients in our series ranged from 32 to 75 years, and all patients were male. Cough and blood-tinged sputum were present in all patients with endobronchial GT. The tumor sizes ranged from 1 to 3 cm. Complete endoscopic resection and laser cauterization via rigid bronchoscopy were achieved in two patients. One patient had incomplete resection of a 3-cm tumor in the segmental bronchus that showed radiological evidence of bronchial wall invasion. This patient subsequently underwent lobectomy seven months after bronchoscopic resection. The fourth patient was lost to follow-up. There was no mortality throughout the follow-up periods that ranged from 2.8 to 42.5 months. Factors favoring successful rigid bronchoscopy resection for endobronchial GT include a benign tumor in the central airways without bronchial wall invasion. Conclusion Endoscopic resection and laser cauterization using rigid bronchoscopy may be a viable option for patients with endobronchial GT when surgery is not practical. Clinical trial number Not applicable.